Parental modelling of eating behaviours: Observational validation of the Parental Modelling of Eating Behaviours scale (PARM). (1st March 2015) - Palfreyman, Zoe; Haycraft, Emma; Meyer, Caroline
Highlights: The Parental Modelling of Eating Behaviours Scale (PARM) was further validated. Maternal feeding practices were consistent across three mealtime observations. Self-reported and observed modelling of eating behaviours were positively related. Various facets of maternal modelling were linked to children's eating behaviours. Maternal modelling linked to lower fussiness and higher food enjoyment in children. Abstract: Parents are important role models for their children's eating behaviours. This study aimed to further validate the recently developed Parental Modelling of Eating Behaviours Scale (PARM) by examining the relationships between maternal self-reports on the PARM with the modelling practices exhibited by these mothers during three family mealtime observations. Relationships between observed maternal modelling and maternal reports of children's eating behaviours were also explored. Seventeen mothers with children aged between 2 and 6 years were video recorded at home on three separate occasions whilst eating a meal with their child. Mothers also completed the PARM, the Children's Eating Behaviour Questionnaire and provided demographic information about themselves and their child. Findings provided validation for all three PARM subscales, which were positively associated with their observed counterparts on the observational coding scheme (PARM-O). The results also indicate that habituation to observations did not change the feeding behaviours displayed by mothers. In addition, observed maternal modelling was significantly related to children's food responsiveness (i.e., their interest in and desire for foods), enjoyment of food, and food fussiness. This study makes three important contributions to the literature. It provides construct validation for the PARM measure and provides further observational support for maternal modelling being related to lower levels of food fussiness and higher levels of food enjoyment in their children. These findings also suggest that maternal feeding behaviours remain consistent across repeated observations of family mealtimes, providing validation for previous research which has used single observations.